Factor 36a^2-84ap+49p^2

Math
36a2-84ap+49p2
Rewrite 36a2 as (6a)2.
(6a)2-84ap+49p2
Rewrite 49p2 as (7p)2.
(6a)2-84ap+(7p)2
Check the middle term by multiplying 2ab and compare this result with the middle term in the original expression.
2ab=2⋅(6a)⋅(-7p)
Simplify.
2ab=-84ap
Factor using the perfect square trinomial rule a2-2ab+b2=(a-b)2, where a=6a and b=-7p.
(6a-7p)2
Factor 36a^2-84ap+49p^2

Download our
App from the store

Create a High Performed UI/UX Design from a Silicon Valley.

Scroll to top